2014
DOI: 10.3310/hsdr02270
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of visual field testing when monitoring patients newly diagnosed with glaucoma: mixed methods and modelling

Abstract: BackgroundVisual field (VF) tests are the benchmark for detecting and monitoring the eye disease glaucoma. Measurements from VF tests are variable, which means that frequent monitoring, perhaps over a long period of time, is required to accurately detect true glaucomatous progression. In 2009, guidelines for the diagnosis and management of glaucoma issued by the National Institute for Health and Care Excellence revealed an absence of research evidence about the clinical effectiveness and cost-effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 112 publications
(193 reference statements)
1
51
0
1
Order By: Relevance
“…Recent research evidence, reflected in clinical guidelines, has suggested that more frequent VF testing would help to identify rapidly progressing patients and this would have both clinical and potential health economic benefits. 32,33 At the same time, this would require a shift in resources, clinician opinion, and patient views about automated perimetry. 34,35 This study clearly shows a worse rate of VF loss was associated with older age and, albeit to a lesser extent, level of VF damage at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research evidence, reflected in clinical guidelines, has suggested that more frequent VF testing would help to identify rapidly progressing patients and this would have both clinical and potential health economic benefits. 32,33 At the same time, this would require a shift in resources, clinician opinion, and patient views about automated perimetry. 34,35 This study clearly shows a worse rate of VF loss was associated with older age and, albeit to a lesser extent, level of VF damage at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, certainly in England, there is a tendency to have a 'one size fits all' approach to monitoring the diagnosed patient. 18 We ought to think more about the use of monitoring resources in glaucoma, especially in those patients who present with more advanced disease as compared with those with little visual loss at diagnosis, or those with ocular hypertension only. Moreover, there appears to be a 'research obsession' with 'pre-perimetric' glaucoma and newer detection technology, but are these really required to prevent visual impairment?…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Allocating perimetry resources correctly and installing perimetry at the centre of glaucoma follow-up is also a challenge. 18 Next, how do we best summarise visual field loss and the worsening of visual field loss? This is often done with a number (or series of numbers).…”
Section: The Burden Of Glaucomamentioning
confidence: 99%
“…l Evaluation of patient experience and the clinical effectiveness and cost-effectiveness of including imaging outcomes with VF testing in managing patients with glaucoma. 12 Patient focus groups indicated that, although patients do not like VF testing, they accept it as a critical part of their care. This research explored the 'diagnostic gain' from including imaging data.…”
Section: (4-5)mentioning
confidence: 99%
“…10,11 The requirement for frequent VF tests over extended periods of time results in delayed identification of vision loss and is a burden to patients and the NHS. 12 The vision loss in glaucoma is a consequence of structural damage to the ONH. 13 Nerve cells in the retina (retinal ganglion cells) transmit light sensitivity information to the brain through fibres that form a layer on the retinal surface, known as the RNFL.…”
Section: Trial Registrationmentioning
confidence: 99%